2016
DOI: 10.1186/s12906-016-1444-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Radix Stemonae concentrated decoction on the lung tissue pathology and inflammatory mediators in COPD rats

Abstract: BackgroundChronic obstructive pulmonary disease (COPD) is a common and frequently occurring respiratory disease. At present, western medicine treatment of COPD mainly focuses on symptomatic treatment. Using Chinese medicines or integrated Chinese and Western medicines to treat stable COPD has significant efficacy. In this study, we aimed to observe the effect of Radix Stemonae concentrated decoction on the lung tissue pathology and inflammatory mediators in COPD rats and explore its possible mechanism.MethodsS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 32 publications
(34 reference statements)
1
8
0
Order By: Relevance
“…In addition, the detection of inflammatory indicators in the lung showed that the levels of TNF-, IL-6, IL-8 and IL-10 from BALF in the PRVC group were significantly lower than those in the VC group, suggesting that excessive airway pressure may lead to the structural destruction of lung tissue with poor compliance, thus causing airway injury. This result is consistent with the results of related literatures [17][18][19][20] .…”
Section: Discussionsupporting
confidence: 94%
“…In addition, the detection of inflammatory indicators in the lung showed that the levels of TNF-, IL-6, IL-8 and IL-10 from BALF in the PRVC group were significantly lower than those in the VC group, suggesting that excessive airway pressure may lead to the structural destruction of lung tissue with poor compliance, thus causing airway injury. This result is consistent with the results of related literatures [17][18][19][20] .…”
Section: Discussionsupporting
confidence: 94%
“…Radix Stemonae, also known as Baibu, is one of the most popular herbal medicines used in many Asian countries, including China, Korea, Japan, Thailand and Vietnam. It has been used for the treatment of various respiratory diseases such as bronchitis, pertussis and tuberculosis [1,2]. It was also used for killing cattle parasites, agricultural pests and domestic insects [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…The present study supports that TLRs (TLR4, TLR2) decrease and phosphorylated (active) IκB (p-IκB) and NF-κB p65 increase in COPD model rats, and further increase pro-inflammatory cytokines, while Feikang granules protect these inflammatory responses. However, whether the Feikang granules also trigger the upstream of anti-inflammatory signaling pathways, such as TGF-β, need to be further investigated [18,25].…”
Section: Discussionmentioning
confidence: 99%
“…A few studies of Feikang Granules on animals have a specific protective effect on vascular endothelial injury in hypoxic pulmonary hypertension [17] and significantly reduce the Transforming Growth Factor β 1 in COPD model Rats [16]. It has been showed that Chinese medicine Radix Stemonae significantly decreases the concentrations of inflammatory mediators TNF-α, IL-8 and LTB4 of COPD model rats [18]. Whether Feikang Granules alleviate the clinical symptoms in COPD patients also involved in the anti-inflammation mechanism remains unclear.…”
Section: Introductionmentioning
confidence: 99%